Film art : an introduction - Bordwell, David, 1947-; Thompson, Kristin, 1950-; Smith, Jeff, 1962- (McGraw-Hill Education, 2020)
"Film Art provides the respected scholarship and analytic tools students need to understand key vocabulary and concepts of film forms, techniques, and history;appreciate a wide variety of classic and contemporary films and the creative choices made by filmmakers to shape the experience of viewers; and analyze films critically and systematically to enrich their understanding and appreciation of any film, in any genre"- Resumé vydavatel
Terminologický slovník
Keywords: filmový průmysl; dějiny filmu; filmová kritika; film; kinematografie; filmová estetika; history of film; film criticism; cinematography; aesthetics of film; učebnice vysokých škol; textbooks (higher)